3-Mercaptopropionic Acid as Corrosion Inhibitor for Carbon Steel in CO2 Aerated 1% NaCl Solution with Buffer Control-pH - Yayan Sunarya (Molekul, 2018)
In this research, 3-Mercaptopropionic acid (MPA) as corrosion inhibitor of carbon steel in CO2 aerated 1% NaCl solution with buffer pH adjustment has been studied by means of electrochemical impedance (EIS) and polarization (Tafel plot). MPA was found to be an effective carbon steel inhibitor. Percentage inhibition efficiency (IE %) calculated by both Tafel plot and EIS, ranged from 85% to 90%. MPA was found to affect the cathodic processes and act as cathodic-type inhibitors. Mechanism of inhibit corrosion by adsorption mechanism leads to the formation of a protective chemisorbed film on the metal surface film which suppresses the dissolution reaction and the hydrogen evolution reaction is activation controlled.